Implementasi Perencanaan Pembelajaran Penjas SMA/SMK Negeri 1 Gombong Kabupaten Kebumen - Zaenulloh, Mohammad; Sulaiman, Sulaiman (Universitas Negeri Semarang, 2023)
The Learning Implementation Plan has not been fully implemented and the implementation of the learning implementation by the teachers of the two schools has not fully referred to the lesson plans made by the teacher, therefore it is necessary to prepare lesson plans so that learning is more systematic and an interesting learning process is created.. The purpose of this study is to examine the process of planning, implementing, and evaluating learning carried out by physical education teachers at SMA Negeri 1 Gombong and SMK Negeri 1 Gombong, Kebumen Regency. This research is using descriptive qualitative approach. Data was collected by using observation, interview, and documentation methods. The results of this study indicate that, 1) Aspects of planning, the teacher has made and has a lesson plan that has been prepared before the learning process takes place. The obstacles experienced by teachers in preparing lesson plans are various, among others, related to the preparation of basic competencies, indicators, to existing facilities and infrastructure. 2) Aspects of implementation, the teacher carries out activities that begin with the introduction, core, and closing. 3) aspects of teacher assessment have carried out affective, cognitive, and psychomotor assessment activities.